AUDITOR INTERNAL DALAM PERSPEKTIF PERILAKU UNTUK KEBERHASILAN TUGAS AUDIT PADA INSTANSI PEMERINTAH DI KABUPATEN PEMALANG - Punjul Tyoso, Jaluanto Sunu; Astuti, Wiwit Erika Windi (Balance : Jurnal Akuntansi dan Bisnis, 2022)
This study examined the behavioral aspects of internal auditors commonly found in the implementation of internal audits. The qualitative with a case study approach was used. The results of this study were the behavioral aspects of internal auditors such as, professional accuracy in fraud prevention, the role of internal audit in Enterprise Risk Management. The behavior of professional care, motivation, competence, and independence roles were in the auditing, due to these behaviors embedded to the internal auditor that produced a quality audit and minimized the occurrence of fraud. The authority of the internal auditor has been formulated. The roles of the internal auditor have not been fully implemented because the quantity of assignments was not proportionally to the quantity of HR this led to still roles were not in accordance with their positions. The obstacles of audit such as difficulty obtaining data, the limited time, and the lack of communication.